The Effect of the Addition of Electrolyte Solutions on the Ferning Patterns of Tears Collected from Normal Eye Subjects - Alanazi, Mana A.; El-Hiti, Gamal A.; Alshehri, Jaber A.; Alhadyan, Ahmed S.; Fagehi, Raied; Masmali, Ali M.; Almubrad, Turki (Optometry and vision science, 2022)
The current study is the first report to describe the improvement of ferning patterns of human tears using electrolyte solutions. The results can help in the production of new artificial tears to improve the quality of tears. This study aimed to investigate the effect of the addition of different volumes of various electrolyte solutions on ferning patterns of human tears. Tear samples (20 μL) were collected from the right eye of 13 subjects (5 men and 5 women) aged 19 to 36 years (27.1 ± 5.1 years) with normal eyes. Then, 1 μL of each tear sample was dried on a microscopic glass slide, and obtained ferns were observed using light microscopy and graded using the 5-point tear ferning (TF) grading scale. Homogenous mixtures of each tear sample (0.5 μL) and different volumes (0.5 to 5 μL) of each electrolyte were prepared. A sample (1 μL) of each mixture was dried, and the ferns obtained were graded and compared with those of the corresponding tears collected from subjects before the addition of electrolyte solutions. After the addition of electrolyte solutions, the TF grades of tears collected from healthy humans were generally improved. Significant (Wilcoxon test) improvements have been seen in the TF grades of the tear samples after the addition of a solution of potassium chloride (P = .03), calcium chloride (P = .01), magnesium chloride hexahydrate (P = .002), and sodium dihydrogen phosphate (P = .002). No significant improvements in the TF grades were seen after the addition of sodium chloride solution (P = .33). Ferning grades of human tears improved with most of the electrolytes used.